National Media Coverage of Hydraulic Fracturing in the United States: Evaluation Using Human and Automated Coding Techniques. Issue 3 (September 2016) - Blair, Benjamin; Heikkila, Tanya; Weible, Christopher M.
Abstract : This article offers an analysis of the national level news media coverage of the risks and benefits surrounding hydraulic fracturing, using two different content analysis methods. First, we complete a manual content analysis on 150 articles by the New York Times, the Wall Street Journal, and USA Today . We examine differences across these newspapers in reporting on environmental, public health, and economic risks and benefits, including the actors who the newspapers cite and whether these actors convey risks and benefits with certainty or uncertainty. Second, we use a semi‐automated coding technique to examine coverage of environmental, environmental damage, public health, and economic topics in 15 nationally distributed newspapers. Overall, we conclude that the two approaches to studying national media content offer some similar insights into how the political leaning of newspapers may result in different coverage of hydraulic fracturing, but manual and automated codings each present distinct strengths and weaknesses in understanding media coverage of this contentious issue.